If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = -3u Solving -24 = -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. -24 + 3u = -3u + 3u Combine like terms: -3u + 3u = 0 -24 + 3u = 0 Add '24' to each side of the equation. -24 + 24 + 3u = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 3u = 0 + 24 3u = 0 + 24 Combine like terms: 0 + 24 = 24 3u = 24 Divide each side by '3'. u = 8 Simplifying u = 8
| -0.0625x^2+2x+10=0 | | 3(4y+1)+5y=10 | | 4x+0.4=0.4 | | Y+-6y+-17=8 | | 81x-2x+2=90 | | 2p+4=p-16 | | -21+-15= | | 2x=45.49 | | 81x-2+2=90 | | 14+7.3=x+12.8 | | -8=u+9 | | 2+0.4y=0.4 | | 5t*=25t | | 7x+4xy=12 | | (7X+5)(2X-2U-3)=EQUATION | | 13s+1s+6s-6=14 | | (15lnx)-(lnx^13)=ln(7x+30) | | 50-3u=17 | | -3x+5=2x-25 | | 486+22n=30n+350 | | 5x^2+4x-12= | | 11p+-4p+-18p+-p-11p=-13 | | 2x+3.5(3)=1.5 | | -y^2+6y=4 | | 90+90+(2x+4)+(3x+29)=360 | | -2+3.5y=1.5 | | 15lnx-lnx^13=ln(7x+30) | | g+-18=-36 | | -4(x)+3=4 | | 14q+-18q=16 | | 3ln(x-7)+5=17 | | 6=-16t^2+50t+100 |